Two new species of Pluteus (Pluteaceae) from India based on morphology and ITS-based phylogeny - Keerthi, V.; Justo, Alfredo; Pradeep, C.k. (Phytotaxa, 2024)
Two new Pluteus species, P. fuscipruinatus and P. chimminiensis belonging to sect. Celluloderma, are described based on specimens collected from Kerala state, India. Maximum Likelihood phylogenetic analysis using nrITS revealed that P. fuscipruinatus belongs to the /ephebeus clade, while P. chimminiensis belongs to the cinereofuscus clade. Detailed descriptions supplemented with field images, microscopic features, phylogenetic analysis, and comparative assessments with allied taxa are provided. A key to the species of Pluteus sect. Celluloderma known to occur in India is also provided.